2021
DOI: 10.1177/1329878x211007176
|View full text |Cite
|
Sign up to set email alerts
|

An intersectional approach to media coverage of politics in New Zealand: The case of Metiria Turei and Paula Bennett

Abstract: This study analyses media coverage of two Māori women politicians in Aotearoa New Zealand. This article adopts an intersectional lens to critically examine the discriminatory ideologies at play in mainstream New Zealand media coverage of Metiria Turei and Paula Bennett. The analysis reveals that although the coverage examined in this article presents the Māori heritage of the two women very differently, the coverage pays close attention to both women’s gender and bodies while simultaneously diminishing their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In Aotearoa New Zealand, research has conclusively demonstrated that negative portrayals of Māori and Pacific are prominent in discourses on health (Hodgetts, Masters, & Robertson, 2004;H. Moewaka Barnes & McCreanor, 2019;Rankine & McCreanor, 2004), politics (Galy-Badenas, Gray, & Cassidy;McConville, Wetherell, McCreanor, & Barnes, 2014), and crime (Barnes, Taiapa, Borell, & McCreanor, 2013;Deckert, 2020;Maydell, 2018;McCreanor et al, 2014;Meek, 2013). However, to our knowledge, only one study has analysed the content of reality-crime shows (Podvoiskis, 2012).…”
mentioning
confidence: 99%
“…In Aotearoa New Zealand, research has conclusively demonstrated that negative portrayals of Māori and Pacific are prominent in discourses on health (Hodgetts, Masters, & Robertson, 2004;H. Moewaka Barnes & McCreanor, 2019;Rankine & McCreanor, 2004), politics (Galy-Badenas, Gray, & Cassidy;McConville, Wetherell, McCreanor, & Barnes, 2014), and crime (Barnes, Taiapa, Borell, & McCreanor, 2013;Deckert, 2020;Maydell, 2018;McCreanor et al, 2014;Meek, 2013). However, to our knowledge, only one study has analysed the content of reality-crime shows (Podvoiskis, 2012).…”
mentioning
confidence: 99%